DEVELOPMENT OF LUBRICATION SYSTEM LEARNING MEDIA BASED ON THE INSTAGRAM APPLICATION - Evan Novrian Jabariel; Yusep Sukrawan; Ibnu Mubarak (Jurnal Dinamika Vokasional Teknik Mesin, 2025)
Instructional media serves as a pivotal tool in facilitating interactions between teachers and students. The effective and efficient learning process can be significantly enhanced through the optimal utilization of these media. However, this ideal has not been fully realized in the learning environment of SMK Negeri 7 Baleendah. To address this gap, this study aimed to develop an optimal instructional medium. The 4-D model was employed as the methodological framework for this research. The developed instructional medium underwent rigorous validation by a panel of five media experts and five material experts. Upon successful validation, the medium was disseminated to students for practical application. The results of the study revealed that the developed medium demonstrated high validity, as assessed using the Content Validity Ratio (CVR) and Content Validity Index (CVI). The CVR analysis of the media experts' ratings yielded a perfect score of 1 for all items, indicating strong content validity. Similarly, the CVI analysis produced a score of 1, further confirming the medium's content validity. The material experts' ratings also exhibited high validity, with CVR scores consistently exceeding 0.50 and CVI scores surpassing 0.83. Subsequent dissemination of the medium garnered positive feedback from the student users. The learning media that has been created can be used by teachers and students.